DESIGN AND EXPERIMENT OF A CLAMP-HOLDING PRECISION MAIZE-SEED-METERING DEVICE - Xuejun Zhang; Jinpeng Cheng; Zenglu Shi; Yunhe Zhang; Meijing Wang (Engenharia Agrícola, 2022)
ABSTRACT To solve the current problems of poor seeding stability and complex maintenance of maize seed-metering devices, a clamp-holding precision maize-seed-metering device is designed. The structure and working principle of the seed-metering device are described, the optimum state of maize seed clamping is analyzed, and the range of each working area of the seed-metering device is determined. The profile and structural parameters of the limit guide plate are designed by analyzing the laws of motion of the seed-picking block. A mechanical model of maize seeds under the critical state in each working area of the seed-metering device is established. The influence of the seed-metering device's rotational speed and the clamping force of the seed-picking block on the seeding performance are analyzed. A physical prototype of the seed-metering device was made for bench tests and field verification tests. The qualified, multiple seeding, and missed seeding rates of the designed seed-metering device were 94.21%, 3.52%, and 2.27%, respectively, meeting the agronomic requirements of maize sowing. The study provides theoretical guidance for designing and optimizing precision maize-seed-metering devices.